Finite element analysis of the shear performance of box-groove interface of ultra-high-performance concrete (UHPC)-normal strength concrete (NSC) composite girder - Farouk, Abdulwarith Ibrahim Bibi; Zhu, Jinsong; Yuhui, Gu (Innovative infrastructure solutions : the official journal of the Soil-Structure Interaction Group in Egypt (SSIGE), 2022)
Ultra-high-performance concrete (UHPC) has been widely used in hybrid structures with normal strength concrete (NSC) due to the high performance of UHPC. However, there is limited knowledge on interface shear performance between UHPC and NSC. This study proposed a shear strength model for a long-span UHPC-NSC composite girder with a groove interface. A finite element model of the UHPC-NSC interfaces was established. The interface shear performance of precast NSC and cast-in-place UHPC with different interfaces, including the box groove, were numerically analyzed and validated by experimental data obtained from a push-off test. The numerical analysis indicates that the reinforcement across the UHPC-NSC interface could effectively improve the ultimate shear resistance of the interface with the groove surface. The eccentric loading distance slightly decreases the ultimate shear resistance. The AFGC-2013 recommendations provide better prediction accuracy than the ACI 318-14 and AASHTO LRFD.